Emerging Trends towards Cyber Safety Mechanism and Our Society - Chouhan, Raksha (Gyan Management Journal, 2015)
Internet usages are increasing rapidly day by day and success in any field of human activity leads to crime that needs systematic mechanism to control it. Cyber Man than has imparted many endowments to humanity but they have come with unexpected pitfalls also. Cyberspace offers a place to perform multiple activities which are prohibited by Law. Mostly it is used for infringing copyright, trafficking in human organs and prohibited drugs, violating individual's privacy, pornography, gambling, hacking, terrorism, money laundering,fraud, software piracy and corporate espionage etc. The failure towards providing trusted secure services in modern computer network technologies has a remarkable socioeconomic impact on global enterprises as well as on individuals. Thus Growing danger from crimes committed against electronic information on computers is alerting us to claim attention in national capitals and requires dedicated legislation on cyber crime to supplement the Indian Penal Code. The basic theme of this research paper is to critically analyze emerging trends for cyber safety mechanism to protect our society and to crack as to how the issue of cyber crimes has been dealt with in the Indian scenario. This paper also examines the reasons behind failure of legal mechanism and also identifies the methods by which cybercrime can be reduced.
Keywords: Cyber Attacks; Cyb er Crimes,; Cyber Safety; Cyber law; I. T Act 2000